Spring weed communities of rice agrocoenoses in central Nepal - Nowak, Arkadiusz; Nowak, Sylwia; Nobis, Marcin (Acta Botanica Croatica, 2016)
Rice field weed communities occurring in central Nepal are presented in this study. The research was focussed on the classification of segetal plant communities occurring in paddy fields, which had been poorly investigated from a geobotanical standpoint. In all, 108 phytosociological relevés were sampled, using the Braun-Blanquet method. The analyses classified the vegetation into 9 communities, including 7 associations and one subassociation. Four new plant associations and one new subassociation were proposed: Elatinetum triandro-ambiguae, Mazo pumili-Lindernietum ciliatae, Mazo pumili-Lindernietum ciliatae caesulietosum axillaris, Rotaletum rotundifoliae and Ammanietum pygmeae. Due to species composition and habitat preferences all phytocoenoses were included into the Oryzetea sativae class and the Ludwigion hyssopifolio-octovalvis alliance. As in other rice field phytocoenoses, the main discrimination factors for the plots are depth of water, soil trophy and species richness. The altitudinal distribution also has a significant influence and separates the Rotaletum rotundifoliae and Elatinetum triandro-ambiguae associations. The study shows that anthropogenic rice fields can harbour relatively rich rush and water vegetation. More than 80 species were noted in the vegetation plots. Several of them are considered to be extremely rare and have been recorded on the world Red List.